2017
DOI: 10.1186/s12913-017-2173-8
|View full text |Cite
|
Sign up to set email alerts
|

Mobile radiography services in nursing homes: a systematic review of residents’ and societal outcomes

Abstract: BackgroundDemographic changes are leading to an ageing population in Europe, and predict an increase in the number of nursing home residents over the next 30 years. Nursing home residents need specialised healthcare services such as radiology due to both chronic and acute illnesses. Mobile radiography, x-ray examinations performed in the nursing homes, may be a good way of providing services to this population. The aim of this systematic review was to identify the outcomes of mobile radiography services for nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 17 publications
1
35
0
4
Order By: Relevance
“…However, earlier research has shown that mobile radiography services facilitate high-quality treatment and care. 16 According to Ranhoff and Linnsund, 6 nursing home residents would in most cases be better off treated in the nursing home. Providing adequate treatment in nursing homes would, in many cases, be easier when the diagnosis is supported by imaging.…”
Section: Quality Of Treatment and Carementioning
confidence: 99%
See 4 more Smart Citations
“…However, earlier research has shown that mobile radiography services facilitate high-quality treatment and care. 16 According to Ranhoff and Linnsund, 6 nursing home residents would in most cases be better off treated in the nursing home. Providing adequate treatment in nursing homes would, in many cases, be easier when the diagnosis is supported by imaging.…”
Section: Quality Of Treatment and Carementioning
confidence: 99%
“…7,9,10,23 Treatment in the nursing home would be the best alternative for most residents because of their poor health and need for a calm and familiar environment. 6,14,16…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations